Respirator - Ahmad Rozlaimi, Raudathul Fathirah; Mhd Fauzi, Nurul Intan Farhana; Othman, Siti Amira (Penerbit UTHM, 2020)
Respirator is a protective device that covers the nose and mouth to protect workers against hazardous atmospheres. These hazardous atmospheres where the work environments have harmful air that comes from dust, fogs, smokes, mists, fumes, and gases. According to the National Institute of Occupational Safety and Health, they recorded that 7% of miners were diagnosed with pneumoconiosis due to the long exposure to dust. In order to reduce this hazard substances, respirators are needed for workers that work in this such environment.